2007
DOI: 10.1590/s1516-35982007000600004
|View full text |Cite
|
Sign up to set email alerts
|

Influência do nitrogênio e do fósforo na produção do capim-braquiária

Abstract: Este experimento foi conduzido para avaliar a produção de MS, a relação folha:colmo, o teor de PB e a eficiência de resposta ao nitrogênio da folha e do colmo do capim-braquiária adubado com diferentes doses de nitrogênio e de fósforo durante o verão. Utilizou-se o delineamento experimental inteiramente casualizado, com três repetições, em esquema fatorial 4 × 3, composto de quatro doses de nitrogênio (N) (0, 100, 200 e 300 kg/ha/ano), utilizando-se o sulfato de amônio, e três doses de P2O5 (0, 50 e 100 kg/ha/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
3
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 13 publications
6
17
3
17
Order By: Relevance
“…After 28 days of regrowth, the leaf and stem production was similar. This result confirms that with increasing pasture age, the leaf-stem ratio increases, leading to greater total dry-matter production and strongly affecting pasture quality (MAGALHÃES et al, 2007).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…After 28 days of regrowth, the leaf and stem production was similar. This result confirms that with increasing pasture age, the leaf-stem ratio increases, leading to greater total dry-matter production and strongly affecting pasture quality (MAGALHÃES et al, 2007).…”
Section: Resultssupporting
confidence: 83%
“…Therefore, liming and phosphate fertilization improve the mineral nutrition of the plant and the nutritional value of the forage and help to maintain the productive capacity of pastures over time (MAGALHÃES et al, 2007). According to the National Research Council (2000), P and Ca are also important animal nutrients, primarily affecting bone development.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature Brachiaria decumbens can produce up to 1800 kg·ha −1 grown in hard conditions of water deficiency, such as savannas [22]. The same species can produce in normal conditions with optimum addition of fertilizers around 3500 kg·ha −1 [39], and 9000 kg·ha −1 [40] of dry mass. Other specie Brachiaria brizantha can produce high quantities of biomass values between 3000 kg·ha −1 [41] and 8000 kg·ha −1 of dry biomass [42]; Brachiaria dictyoneura can produce more than 5700 kg·ha −1 when this crop is grown alone, without consortium [43].…”
Section: Discussionmentioning
confidence: 99%
“…One of the essential production factors is an adequate forage fertilization, to increase productivity and, consequently, expand the share of Brazil in the supply chain of primary agricultural products at the global level (Magalhães et al, 2007). Fagundes et al (2005) reported that soil N contents are usually insufficient to meet the demand of grasses.…”
Section: Introductionmentioning
confidence: 99%